Prarancangan Pabrik Dodekilbenzena dari Dodekena dan Benzena dengan Proses DETAL Kapasitas 65.000 ton/tahun - Budi, Putri Maharani, Emi Erawati, S.T., M.Eng, Eni Budiyati, S.T., M.Eng (2016)
Surfactant is a kind of raw material that used as soap and detergent produciton. One of the most usable surfactant is sodium dodecylbenzene sulphonate which produced from linear alkyl benzene (LAB). Dodecylbenzene, the most produced LAB, are made from dodecene and benzene. This dodecylbenzene are very environmentaly friendly. Dodecylbenzene producing process with DETAL are carried out with temperatur of 150oC in singletube fixed bed reactor. The benzene needs are 2.733,70 kg/h and dodecene needs are 6.139,44 kg/h. The main product is dodecylbenzene with 8.207,07 kg/h massflow and side product is didodecylbenzene with 452,61 kg/h. The supporting process unit in this dodecylbenzene factory are water producing unit with 46.912,83 kg/h capacity, steam producing unit with 8.478,37 kg/h, electricity unit with 472,84 kW, compressed air supply unit 150 m3/h, and MFO fuel supply unit with 711,38 kg/h capacity. This factory are established in Cilacap, Central Java with 156 employees. The company are classified as Limited Liability Company which is the capital cost are covered by stocks selling. This dodecylbenzene factory needs 475.082.291.012 rupiahs fixed capital and 153.829.169.489 rupiahs working capital. The economical analysis result shows that the profit before tax are 330.098.382.068 rupiahs per year, profit after tax are 247.573.786.551 rupiahs per year, Return on investment (ROI) before tax are 69,50%, ROI after tax are 52,10%, Pay out time (POT) before tax are 1,26 years, POT after tax are 1,16 years, Break even point (BEP) are 41,99% and Shut down point (SDP) are 28,63% with Discounted cash flow (DCF) are 20%, so the company are feasible to establish. Keywords : Dodecylbenzene, fixedbed singletube, DETAL,